Would you believe an intoxicated witness? The impact of witness alcohol intoxication status on credibility judgments and suggestibility - Bartlett, Georgina; Gawrylowicz, Julie; Frings, Daniel; Albery, Ian P. (Frontiers in Psychology, 2022)
Memory conformity may occur when a person’s belief in another’s memory report outweighs their belief in their own. Witnesses might be less likely to believe and therefore take on false information from intoxicated co-witnesses, due to the common belief that alcohol impairs memory performance (Monds et al. 2021). This paper presents an online study in which participants (n = 281) watched a video of a mock crime taking place outside a pub that included a witness either visibly consuming wine or a soft drink. Participants then read a statement from the witness that varied in the number of false details it contained before being asked to recall the crime. We found that the intoxicated witness was regarded as significantly less credible, but participants were not less likely to report misinformation from them. This suggests that intoxication status impacts one’s perception of how credible a source is, but not one’s ability to reject false suggestions from this source. Our findings reinforce the importance of minimising co-witness discussion prior to interview, and to not to assume that people automatically (correctly or not) discount information provided by intoxicated co-witnesses.